Clopidogrel with Aspirin versus Aspirin Alone following Intravenous Thrombolysis in Minor Stroke: A 1-Year Follow-Up Study - Hai-Ming Cao; Hui-Wen Lian; Yan E; Rui Duan; Jun-Shan Zhou; Xiang-Liang Chen; Teng Jiang (Brain Sciences, 2022)
Objective: The objective of this study was to investigate the long-term effect of dual antiplatelet therapy (DAPT) using clopidogrel plus aspirin versus aspirin monotherapy after intravenous thrombolysis on functional outcomes in patients with minor stroke. Methods: Patients with acute ischemic stroke with a National Institutes of Health Stroke Scale score ≤ 5 who received either DAPT or aspirin monotherapy following recombinant tissue plasminogen activator intravenous thrombolysis were studied. Data recorded between January 2017 and December 2020 were retrospectively analyzed. The primary efficacy outcome was functional improvement at 1 year, measured by a 1-point decrease across modified Rankin Scale (mRS) scores. Secondary outcomes included complete rehabilitation (mRS = 0), an excellent outcome (mRS = 0–1), and a favorable outcome (mRS = 0–2) at 1 year, as well as the rates of stroke recurrence and all-cause mortality within 1 year. Results: A total of 238 patients were included, and follow-up data were available for 205 patients (86.1%). The distribution of 1-year outcomes on the mRS favored DAPT over aspirin monotherapy (adjusted common odds ratio (OR), 2.19; 95% confidence interval (CI), 1.12–4.28; p = 0.022). Patients who received DAPT, compared with those receiving aspirin alone, were more likely to achieve complete rehabilitation (adjusted OR, 2.44; 95% CI, 1.21–4.95; p = 0.013) at the 1-year follow-up. Additionally, the percentages of an excellent outcome and a favorable outcome did not differ, and the rates of stroke recurrence and all-cause mortality were comparable during the 1-year follow-up. Conclusions: Clopidogrel with aspirin following intravenous thrombolysis was associated with improved functional outcome at the 1-year follow-up for patients with minor stroke, and it did not increase the stroke recurrence rate and mortality.